Changeling illusion - Finlayson, Marina ([West Pennant Hills, New South Wales] : Finesse Solutions, 2019)
"All I want is a little alone time with my hot new boyfriend. That shouldn’t be too much to ask, but Kellith, the Lord of Summer, keeps sending his assassins after me. Since it’s kill or be killed, I need to bring him down—but how do I take on one of the most powerful fae in all the Realms? The answer lies in the Realm of Illusion, the fabulously wealthy home of the tricksters and the shapeshifters. When Kellith stole its wealth for himself, he thought he’d destroyed them all. But a few exiles remain, and an explosive secret reveals that my fate is tied to theirs. If I can bring the exiles home, Kellith will lose the lot. But if I fail, Illusion disappears forever—and Kellith’s next assassin will take my head." -- Back cover.
Keywords: Fantasy fiction; Australian; Fantasy fiction